Compact With The Charter And Laws Of The Colony Of New Plymouth 184 (1836) - (:unkn) unknown (My University, 1677)
"It is enacted by the Court That the order of Court made Anno 1644 allowing Matchcockes be repealed ; and that all psons required by the lawes of this Collonie to keep and maintaine armes ; be att all times provided with sufficient fix feir lockes or snaphance musketts or other servicable peeces not exceeding four foot and an halfe longe ; nor under Colliver bore"
Keywords: REQUIRED POSSESSION